Inherent bioelectrical parameters of hundreds of thousands of single leukocytes based on impedance flow cytometry. Issue 8 (19th February 2022) - Tan, Huiwen; Wang, Minruihong; Zhang, Yi; Huang, Xukun; Chen, Deyong; Li, Yueying; Wu, Min‐Hsien; Wang, Ke; Wang, Junbo; Chen, Jian
Abstract: As label‐free biomarkers, bioelectrical properties of single cells have been widely used in hematology analyzers for 3‐part differential of leukocytes, in which, however, instrument dependent bioelectrical parameters (e.g., DC/AC impedance values) rather than inherent bioelectrical parameters (e.g., diameter Dc, specific membrane capacitance Csm and cytoplasmic conductivity σcy ) were used, leading to poor comparisons among different instruments. In order to address this issue, this study collected inherent bioelectrical parameters from hundreds of thousands of white blood cells based on a home‐developed impedance flow cytometry with corresponding 3‐part differential of leukocytes realized. More specifically, leukocytes were separated into three major subtypes of granulocytes, monocytes and lymphocytes based on density gradient centrifugation. Then these separated cells were aspirated through a constriction‐microchannel based impedance flow cytometry where inherent bioelectrical parameters of Dc, Csm and σcy were quantified as 9.8 ± 0.7 μm, 2.06 ± 0.26 μF/cm 2, and 0.34 ± 0.05 S/m for granulocytes (ncell = 134, 829); 10.4 ± 1.0 μm, 2.45 ± 0.48 μF/cm 2, and 0.42 ± 0.08 S/m for monocytes (ncell = 40, 226); 8.0 ± 0.5 μm, 2.23 ± 0.34 μF/cm 2, and 0.35 ± 0.08 S/m for lymphocytes (ncell = 129, 193). Based on these inherent bioelectrical parameters, neural pattern recognition was conducted, producing a high "classification accuracy" of 93.5% in classifying these three subtypes of leukocytes. These results indicate that as inherent bioelectrical parameters, Dc, Csm, and σcy can be used to electrically phenotype white blood cells in a label‐free manner.